A review with meta-analysis of observational studies for survival following off-pump coronary artery bypass versus drug-eluting stent implantation. (2nd March 2014) - Takagi, Hisato; Watanabe, Taku; Mizuno, Yusuke; Kawai, Norikazu; Umemoto, Takuya
Abstract: To determine whether off-pump coronary artery bypass (OPCAB) improves survival over drug-eluting stent (DES) implantation, we performed a review with meta-analysis of exclusive OPCAB versus DES. Databases including MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were searched through October 2013 using Web-based search engines (PubMed and OVID). Studies that met the following criteria were considered for inclusion: the design was a randomized controlled trial or observational comparative study; the study population was patients with any coronary artery disease; patients were assigned to OPCAB versus DES and outcomes included all-cause mortality at ≥1 years. Our exhaustive search identified no randomized trial and 10 observational studies of OPCAB versus DES. A pooled analysis demonstrated no statistically significant difference in all-cause mortality between OPCAB and DES (hazard ratio, 0.94; 95% confidence interval, 0.76–1.15; P = 0.55). In general, exclusion of any single study from the analysis did not substantially alter the overall result of our analysis. There was no evidence of significant publication bias. In conclusion, OPCAB may not improve survival over DES despite greater number of treated vessels in OPCAB than in DES or greater number of distal anastomosis in OPCAB than that of implanted stents in DES.